Conductivity and permittivity of dispersed systems with penetrable particle-host interphase - Sushko, M.Ya.; Semenov, A.K. (Condensed Matter Physics, 2013)
A model for the study of the effective quasistatic conductivity and permittivity of dispersed systems with particle-host interphase, within which many-particle polarization and correlation contributions are effectively incorporated, is presented. The structure of the system’s components, including the interphase, is taken into account through modelling their low-frequency complex permittivity profiles. The model describes, among other things, a percolation-type behavior of the effective conductivity, accompanied by a considerable increase in the real part of the effective complex permittivity. The percolation threshold location is determined mainly by the thickness of the interphase. The “double” percolation effect is predicted. The results are contrasted with experiment. Запропоновано модель для вивчення ефективних квазiстатичних провiдностi та дiелектричної проникностi дисперсних систем iз вiльно-проникним мiжфазним шаром мiж частинками та середовищем, яка ефективно враховує багаточастинковi поляризацiйнi та кореляцiйнi ефекти. Структура компонентiв системи, включаючи мiжфазний шар, враховується шляхом моделювання профiлiв їх низькочастотної комплексної дiелектричної проникностi. Модель, зокрема, описує перколяцiйно-подiбну поведiнку ефективної провiдностi, що супроводжується суттєвим зростанням дiйсної частини ефективної комплексної проникностi системи. Положення порогу перколяцiї визначається головним чином товщиною мiжфазного шару.
Передбачено ефект “подвiйної” перколяцiї. Результати порiвняно з експериментом.